STRATEGI PEMBERDAYAAN EKONOMI PESANTREN DAN PENGUATAN DAYA SAING INDUSTRI HALAL DALAM UPAYA PERTUMBUHAN EKONOMI INDONESIA - Supeno, Edy Imam (EKSYAR: Jurnal Ekonomi Syari'ah & Bisnis Islam, 2019)
Indonesia must be in order to prepare the human resources competitive and global-quality. In order to be able to survive and can take advantage of existing opportunities, then the economic empowerment of the pesantren must increase the competitiveness of the halal industry to increase the competitiveness so that it must have an entrepreneurial spirit and the spirit of innovation owned must Capable of being the driving motor to improve the competitiveness of halal industry. By increasing the competitiveness of the industry, it will in turn encourage competitiveness. To be able to maintain the economic existence of the pesantren then it takes a strategy, one of them by creating a variety of advantages and peculiarities generated and need to be done collaboration by involving Pesantren especially in terms of Transfer of expertise to industry members, in incubator containers in order to help improve better performance, both in mentoring management and other skills. Therefore, with the collaboration, it will bring influence in many aspects and potentially able to provide a large economic contribution through added value, job field and foreign exchange, but also able to make a great contribution in Structural transformation of the nation toward the modernization of people's lives that support the formation of national competitiveness.